If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + 15 = 78 Reorder the terms: 15 + z = 78 Solving 15 + z = 78 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + z = 78 + -15 Combine like terms: 15 + -15 = 0 0 + z = 78 + -15 z = 78 + -15 Combine like terms: 78 + -15 = 63 z = 63 Simplifying z = 63
| -50=-4x-20-2x | | 9+5(2w-1)=-3(2w-2)+2w | | 14x-21=15x-5 | | 2x-26=-x+7 | | y=3x+100 | | 5-2ex=3 | | 5x+25(3x)=160 | | 19k-k= | | 9x-176=2x-8 | | 6+30x=20x+22 | | 1+4x=-4+13x | | 2a+5+3a=40 | | 7-9n-17= | | (.5)(x)(x-3)=20 | | 1.3x-6= | | 5x+14=-56-5x | | x+31+61=5x-22 | | 1x/4=8(x-3) | | -3p-4+4p+8=x | | r+10=22 | | 2b-10=b | | 25x+15y=305 | | 9x+11x=180 | | B=2b-10 | | 5abcdefg=6abcdefg-2a+3b | | 10x^3+2y=0 | | 12x+2x=7 | | 0=64x^2-36 | | 2x+y=X | | 6x+9=4x-7 | | a(abc)= | | 63=x-27 |